El grillo, el oso y el nino plantan un jardin = a bug, a bear, and a boy plant a garden - McPhail, David, 1940- (New York : Scholastic, 2001)
Three friends learn, love, and play together.
English and Spanish translations bound back to back (upside down to each other)
Cover title.
Keywords: Gardening -- Fiction; Spanish language materials -- Bilingual; Friendship -- Fiction; Bears -- Fiction; Insects -- Fiction